An Analogue Experiment on Pervious Concrete Subject to Dust Fall Blocking - Lin, Qijian; Choufu, Liang (Civil Engineering Journal, 2018)
Increased urbanization comes with increased traffic volume which gradually decrease the draining effect of porous asphalt concrete through porosity blocking. This study aims to discuss clogging as a result of dust or sand and the subsequent changes at the permeability function after rainfall. Four groups of pervious concrete mixtures were prepared. Aggregates were coarse and fine bottom ashes from the refuse incinerator. Prior to conducting the experiments, the permeability in the groups ranged from 1399.75 ~ 1412.91 ml/15sec. We adopted the 2011 average monthly dust fall in Pingtung County and magnified it by 10 and 20 times to simulate natural dust fall and clump dust fall on the pavement. Ruling out other factors, our results suggest that natural dust fall has little influence on the water permeability of pervious concrete. Water permeability was reduced sharply when the natural dust fall was increased 15 times. Moreover, it never surpassed the 400 ml/15sec minimum of the Japanese porous pavement technical indicator.